Linear electromagnetic wave equations in materials - Starke, Ronald; Schober, Giulio Albert Heinrich (Photonics and nanostructures, 2017)
After a short review of microscopic electrodynamics in materials, we investigate the relation of the microscopic dielectric tensor to the current response tensor and to the full electromagnetic Green function. Subsequently, we give a systematic overview of microscopic electromagnetic wave equations in materials, which can be formulated in terms of the microscopic dielectric tensor.
Gesehen am 14.09.2018